Physical performance limitations in adolescent and adult survivors of childhood cancer and their siblings. - Corina S Rueegg (Public Library of Science (PLoS), 2012)
Purpose This study investigates physical performance limitations for sports and daily activities in recently diagnosed childhood cancer survivors and siblings. Methods The Swiss Childhood Cancer Survivor Study sent a questionnaire to all survivors (≥ 16 years) registered in the Swiss Childhood Cancer Registry, who survived >5 years and were diagnosed 1976-2003 aged <16 years. Siblings received similar questionnaires. We assessed two types of physical performance limitations: 1) limitations in sports; 2) limitations in daily activities (using SF-36 physical function score). We compared results between survivors diagnosed before and after 1990 and determined predictors for both types of limitations by multivariable logistic regression. Results The sample included 1038 survivors and 534 siblings. Overall, 96 survivors (9.5%) and 7 siblings (1.1%) reported a limitation in sports (Odds ratio 5.5, 95%CI 2.9-10.4, p<0.001), mainly caused by musculoskeletal and neurological problems. Findings were even more pronounced for children diagnosed more recently (OR 4.8, CI 2.4-9.6 and 8.3, CI 3.7-18.8 for those diagnosed <1990 and ≥ 1990, respectively; p=0.025). Mean physical function score for limitations in daily activities was 49.6 (CI 48.9-50.4) in survivors and 53.1 (CI 52.5-53.7) in siblings (p<0.001). Again, differences tended to be larger in children diagnosed more recently. Survivors of bone tumors, CNS tumors and retinoblastoma and children treated with radiotherapy were most strongly affected. Conclusion Survivors of childhood cancer, even those diagnosed recently and treated with modern protocols, remain at high risk for physical performance limitations. Treatment and follow-up care should include tailored interventions to mitigate these late effects in high-risk patients.